2015
DOI: 10.3389/fpsyg.2015.00864
|View full text |Cite
|
Sign up to set email alerts
|

Quantity yields quality when it comes to creativity: a brain and behavioral test of the equal-odds rule

Abstract: The creativity research community is in search of a viable cognitive measure providing support for behavioral observations that higher ideational output is often associated with higher creativity (known as the equal-odds rule). One such measure has included divergent thinking: the production of many examples or uses for a common or single object or image. We sought to test the equal-odds rule using a measure of divergent thinking, and applied the consensual assessment technique to determine creative responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 47 publications
2
32
0
1
Order By: Relevance
“…Also noteworthy in this context are the highly significant and positive correlations between fluency and overall originality (Spearman's rho = 0.461, p < 0.001) as well as fluency and peak originality (Spearman's rho = 0.746, p < 0.001), which is consistent with previous findings that higher ideational output (fluency) is associated with greater originality in creative thought (Jung et al 2015) (Fig. 3).…”
Section: Findings: Overall Impact Of Inductionssupporting
confidence: 90%
“…Also noteworthy in this context are the highly significant and positive correlations between fluency and overall originality (Spearman's rho = 0.461, p < 0.001) as well as fluency and peak originality (Spearman's rho = 0.746, p < 0.001), which is consistent with previous findings that higher ideational output (fluency) is associated with greater originality in creative thought (Jung et al 2015) (Fig. 3).…”
Section: Findings: Overall Impact Of Inductionssupporting
confidence: 90%
“…Although the cerebral substrates of associative processing are not elucidated, recent evidence supports the role of the default mode network (DMN) in unconstrained associative thinking [40 ] and more broadly in spontaneous cognition [41] including mind wandering [42,43] and contextual associations [44]. Several studies have shown that the morphometry and functional connectivity of DMN regions correlate with creative performance [45][46][47][48][49][50][51]. Consistent with the role of semantic associations in creativity, semantic memory regions are also important for creative abilities [11,27,28] and have both overlaps and functional interactions with the DMN that remain to be clarified [20,52,53].…”
Section: Recent Cognitive and Neuroimaging Findingsmentioning
confidence: 99%
“…Participants were also administered a variety of tests tapping creativity that will not discussed here (see Ryman et al, 2014;Jung et al, 2015). No prior studies with this data set have explored either spatial or verbal ability.…”
Section: Cognitive Assessmentmentioning
confidence: 99%